Evaluation of pea varieties based on correlation of quantitative traits and indices - О. І. Присяжнюк; Л. В. Король (Plant Varieties Studying and Protection)
Purpose. To evaluate pea plants productivity and determine the degree of correlation among the main agronomic characters in pea varieties. Methods. Structural and statistical analysis. Results. Evaluation of pea samples in terms of indices of plant productivity elements level based on correlation analysis and single-factor indices appliance provided insight into the ratio of one trait share per unit of another one. It was defined that some correlations among the elements of productivity was not only moderate and weak, but they also changed their sign that could be the evidence of growth conditions influence on structural relationships between some traits and, consequently, redistribution of their contributions to the formation of variety productivity. Positive and very close relationship of many traits was revealed, particularly between plant height and the height of the plant up to the first bean, the number of nodes and the number of sterile nodes (r = 0,95–0,97). Methodological aspects of the variety model creation were considered, that may be useful not only in pea breeding but also for improving the technology of its cultivation. Conclusions. Correlation relationships were established between the number of beans and the number of fruiting nodes and the number of carpophores containing 2 beans (r = 0,86–0,88), seed mass and plant mass (r = 0,81), the number of seeds per plant and plant mass and seed mass per plant (r = 0,78–0,81), the number of certified seeds and the number of seeds per plant (r = 0,84), the average number of beans per fertile node and the number of carpophores containing 2 beans (r = 0,74) that makes it possible to use them in assessing the productivity of plants.